Galactic Cosmic Irradiation Alters Acute and Delayed Species-Typical Behavior in Male and Female Mice - Stephanie Puukila; Olivia Siu; Linda Rubinstein; Candice G. T. Tahimic; Moniece Lowe; Steffy Tabares Ruiz; Ivan Korostenskij; Maya Semel; Janani Iyer; Siddhita D. Mhatre; Yasaman Shirazi-Fard; Joshua S. Alwood; et al. (Life, 2023)
Exposure to space galactic cosmic radiation is a principal consideration for deep space missions. While the effects of space irradiation on the nervous system are not fully known, studies in animal models have shown that exposure to ionizing radiation can cause neuronal damage and lead to downstream cognitive and behavioral deficits. Cognitive health implications put humans and missions at risk, and with the upcoming Artemis missions in which female crew will play a major role, advance critical analysis of the neurological and performance responses of male and female rodents to space radiation is vital. Here, we tested the hypothesis that simulated Galactic Cosmic Radiation (GCRSim) exposure disrupts species-typical behavior in mice, including burrowing, rearing, grooming, and nest-building that depend upon hippocampal and medial prefrontal cortex circuitry. Behavior comprises a remarkably well-integrated representation of the biology of the whole animal that informs overall neural and physiological status, revealing functional impairment. We conducted a systematic dose-response analysis of mature (6-month-old) male and female mice exposed to either 5, 15, or 50 cGy 5-ion GCRSim (H, Si, He, O, Fe) at the NASA Space Radiation Laboratory (NSRL). Behavioral performance was evaluated at 72 h (acute) and 91-days (delayed) postradiation exposure. Specifically, species-typical behavior patterns comprising burrowing, rearing, and grooming as well as nest building were analyzed. A Neuroscore test battery (spontaneous activity, proprioception, vibrissae touch, limb symmetry, lateral turning, forelimb outstretching, and climbing) was performed at the acute timepoint to investigate early sensorimotor deficits postirradiation exposure. Nest construction, a measure of neurological and organizational function in rodents, was evaluated using a five-stage Likert scale ‘Deacon’ score that ranged from 1 (a low score where the Nestlet is untouched) to 5 (a high score where the Nestlet is completely shredded and shaped into a nest). Differential acute responses were observed in females relative to males with respect to species-typical behavior following 15 cGy exposure while delayed responses were observed in female grooming following 50 cGy exposure. Significant sex differences were observed at both timepoints in nest building. No deficits in sensorimotor behavior were observed via the Neuroscore. This study revealed subtle, sexually dimorphic GCRSim exposure effects on mouse behavior. Our analysis provides a clearer understanding of GCR dose effects on species typical, sensorimotor and organizational behaviors at acute and delayed timeframes postirradiation, thereby setting the stage for the identification of underlying cellular and molecular events.